Variable Speed Drive For Brushless DC Compressor - Tay, Siang Hui (2003)
This paper presents variable speed drive method for DC Brushless compressor. The trend for air conditioning system is aiming for energy efficiency. This is achieved by utilizing a more efficient compressor and variable speed drive method. As the Compressor is dealing with high variance of temperature range, conventional sensored method for driving a Dc Brushless motor is not practical. A sensor-less method is utilized for this system by detecting the back EMF.